3D N-doped graphene aerogel sponge-loaded CoS2 co-catalytic Fenton system for ciprofloxacin degradation. (20th December 2022) - Shi, Yueyue; Hu, Yongyou; Wang, Yao; Li, Xian; Xiao, Chun; Liu, Jingyu; Chen, Yuancai; Cheng, Jianhua; Zhu, Xiaoqiang; Wang, Guobin; Xie, Jieyun
Abstract: To avoid the loss of powder co-catalysts in metal sulfide-based co-catalytic Fenton process, we prepared a 3D N-doped graphene aerogel sponge-loaded CoS2 (SCG) and carried out a comparative study of ciprofloxacin (CIP) degradation in SCG/Fenton system, powdered CoS2 /Fenton system, and conventional Fenton system. The results showed that SCG co-catalytic performance was comparable to that of powdered CoS2, the basic structure of SCG did not change after 10 times repeated experiments, and the leaching amount of Co x+ was less than 0.1 mg/L. Compared with conventional Fenton system, the content of Fe 2+ in SCG/Fenton system and powdered CoS2 /Fenton system increased from 1.05 mg/L to 8.2 mg/L and 7.9 mg/L, and the decomposition rate of H2 O2 increased from 31.9% to 50.8% and 53.1%. The degradation rate constant of SCG/Fenton system was 0.1915 min −1, 5.7 times that of Fenton system and 1.2 times that of powdered CoS2 /Fenton system, and SCG/Fenton system had a strong anti-interference ability against Cl −, NO3 − and humic acid. 1 O2 and ·OH played a leading role in CIP degradation. S 2− and S2 2− on SCG surface acted as electron donors to accelerate Fe 3+ /Fe 2+ conversion. The ecotoxicity of CIP degradation products was effectively eliminated. This study provides a reference for designing of 3D co-catalyst and a model for the application of co-catalytic Fenton system. Highlights: A novel 3D SCG co-catalyst was synthesized. Accelerating Fe 3+ /Fe 2+ cycle and improving H2 O2 decomposition rate by SCG/Fenton system. Metal leaching reduced and co-catalytic stability enhanced in SCG/Fenton system. Efficient mineralization and detoxification of CIP was achieved.